Estudio de los contenidos y diseño de los diarios de Loja versión digital y la forma de navegación de los usuarios de la ciudad de Loja, periodo septiembre 2012 - agosto 2013. Propuesta Alternativa - Guerrero Villegas, Ulvio Yasmani (2016)
The raised research, search through a study of the contents and design of the dailies of Loja, digital version; understand the shortcomings that exist in the processing of information these and how it affects in the form of user navigation. A fleeting analysis of the Crónica and Centinela dailies, in digital format, he showed the possible problems in the management of digital journalism, which they were verified at on completion of the investigation. Among the objectives raised, we set out to analyze comparatively, the contents of the dailies investigated; likewise if they met the characteristics mentioned by experts in digital journalism. Another objective was to examine the design of the media in the digital version and how to navigate the user. Real data was obtained; the techniques: 1) observation of the dailies for several days consecutively and interviews with leading researchers of digital journalism, 2) allowed to find flaws in the content and design of the papers examined; 3) applying survey of 250 readers of newspapers in the city of Loja, he helped with data on how the user navigates, also what the possible problems that limit the frequent access of the reader. The results show weaknesses in the management of content, similar wording and structure than its predecessor (the newspaper) and little use of the tools provided by the web. The designs of the investigated media need a redesign according to the needs of readers. In conclusion the results, limited user assistance. Keywords: Digital journalism, User, design, content and navigation.